Work from Home Proclivity: A Year into Covid-19 Pandemic - Daniella Cynthia Sampepajung; Insany Fitri Nurqamar; Muhammad Nurhadi N (University of Merdeka Malang, 2021)
All forms of formal education were abruptly shifted into online-learning when Covid-19 hit globally. This unexpected change has forced education practitioners to adapt and conduct their work remotely in order to minimize the virus spread. However, sudden changes are seldom arduous and work from home came with its many challenges. This research seeks to examine the working conditions and job requirements, the time and task management, work related stress, performance at work lecturer’s experience during online-learning and their inclination towards work from home in the future. This research is an exploratory study and the data is analyzed with a statistic descriptive method to describe the phenomenon. Using online questionnaire, a total of 120 lecturers responded. The study discovers that lecturers find the conditions of work from home to be acceptable, they are able to organize their task and time to some extent, and it does not affect their work performance and does not have a negative impact on their stress level. In the future, the lecturers will feel neutral about work from home after the pandemic subsidence. More are leaning towards going back to work in office settings, but open to do hybrid-working, which is a combination of work from office and work from home.